NATIONAL ATLAS OF THE ARCTIC - Nikolay S. Kasimov; Vladimir M. Kotlyakov; Dmitry N. Krasnikov; A. N. Krayukhin; Vladimir S. Tikunov (Geography, Environment, Sustainability, 2018)
The National Atlas of the Arctic is a set of spatio-temporal information about the geographic, ecological, economic, historical-ethnographic, cultural, and social features of theArcticcompiled as a cartographic model of the territory. The Atlas is intended for use in a wide range of scientific, management, economic, defense, educational, and public activities. The state policy of theRussian Federationin the Arctic for the period until 2020 and beyond, states that the Arctic is of strategic importance forRussiain the 21st century. A detailed description of all sections of the Atlas is given. The Atlas can be used as an information-reference and educational resource or as a gift edition.